Sorption Mechanism of Cd(II) and Zn(II) onto Modified Palm Shell - Shilpi Kushwaha; Padmaja Sudhakar (Adsorption Science & Technology)
A series of adsorbents were prepared from palm shell powder (PSP) at different thermochemical conditions. APSP was prepared by treating PSP with H 2 SO 4 , PAPSP by further modification of APSP with K 2 S 2 O 8 at 150 °C and 9AAC by thermal activation of APSP at 900 °C. Fourier transform infrared spectroscopy analysis revealed similarity of functional groups in PSP, APSP and PAPSP, suggesting that functional groups are retained during chemical or physical treatment of PSP at 150 °C. A wide pH range (3–8) was found suitable for cadmium and zinc adsorption. The adsorption of Cd 2+ and Zn 2+ was found to be feasible, spontaneous, exothermic, and could be described by the pseudo-second-order kinetic model as well as by Langmuir and Freundlich isotherm models. The maximum adsorption capacity was found to be 363.636 and 238.095 mg/g for Cd 2+ and Zn 2+ , respectively, using PAPSP. Desorption was achieved using HCl and EDTA for Cd 2+ and Zn 2+ , respectively.